Characterization of Degradation Products of Guanfacine Hydrochloride API: Development and Validation of a Stability-indicating Reversed Phase UHPLC Method (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Guanfacine Hydrochloride API was subjected to forced degradation studies under various conditions of hydrolysis (acidic, alkaline, and neutral/water), oxidation, photolysis, and thermal. A short and simple, reverse phase UHPLC method was developed on a Shimadzu, Shimpack GIST, C18, (100 × 2.1) mm, 3.0 μm column. The gradient method consisted of 0.1% orthophosphoric acid as mobile phase A and acetonitrile as mobile phase B. The flow rate of the mobile phase was 0.3 mL/min. The method was validated using ICH guidelines considering the parameters solution stability, specificity, DL/QL, linearity, accuracy, precision and robustness. The drug was found highly sensitive to alkaline conditions and showed significant degradation. The drug was found sensitive to acidic degradation conditions. Slight degradation was observed in oxidative and water conditions. The drug was found to be stable in thermal and photolytic conditions. The mass compatible UHPLC method was prepared by simply substituting the orthophosphoric acid with formic acid in the mobile phase. Characterization of two major degradation products (DPs) was done. DP1 was characterized with LC–Q-TOF-MS/MS in combination with accurate mass measurements. DP2 was isolated and characterized with NMR, IR and HRMS spectroscopic techniques. The mechanisms of the formation of DPs were proposed.